Criterios de valoración de comunidades vegetales terrestres en el espacio natural de Calblanque (Murcia, SE España) - Esteve M.A.; Ramírez L. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The plant communities of the coastal area of Calblanque (Murcia, SE. Spain) have been evaluated from an ecological approach, using criteria of rarity inside the area (floristic singularity), rarity outside the area (endemismes and threat degree), and structure (stratification and cover), and naturalness (proximity to the potential vegetation). Among the results of the study, the value of the limestone shrub communities, salt marsh vegetation and relict Quercus rotundifolia patches are pointed out.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)